Kickback [compact disc, unabridged] - Parker, Robert B., 1932-2010 (Robert B. Parker's Spenser novel series, 2015)
After setting up a prank twitter account for his vice principal, Dillon Yates is facing criminal charges, Judge Scali is notorious for handing out tough sentences for minor infractions and Dillon's mother is determined to find out why so she hires P.I. Spenser.